THE DEVELOPMENT OF BRITISH ADMINISTRATION IN EKITILAND, 1915 - 1951 (1995)
The thesis focuses attention on the development of British Administration in Ekitiland from 1915-1951, It discusses the British occupation of Ekiti- land and analyses the efforts made by the British to consolidate their administration through the creation of a centralised political authority. It examines the administrative structures evolved and observes that the Ekiti Oba were generally used as Instruments of British Administration, It is shown that under the new political dispensation, the Oba virtually became ciphers in the hands of British Administrative Officers. It is argued that some of the responsibilities assigned to the Oba eroded their traditional power, authority, status and prestige. The thesis also examines the efforts made at creating a central Administration in Ekitiland between 1920 and 1936, The attendant problems of this political experiment are discussed. In particular, the political agitations for secession, autonomy and other political reforms by some communities such as Ado-Ekiti, Akure, Igbara-Odo, Ilawe, Osi etc between 1938 and 1946 are discussed, It argues that these agitations not only threatened political Integration in Ekitiland but also contributed largely to the failure of central Administration put in place by the Colonial Government. The re-organisation efforts made by the British to re-invigorate their tottery administration in Ekitiland between 1946 and 1951 are analysed. The new political dispensation, which was a shift from a rigid centralisation of political authority that was unpalatable to Ekiti Oba to that of loose centralised Administration which allowed them (the Oba) to retain their sovereignty, succeeded to a large extent up to 1951. The economic dimension of British Administration in Ekitiland during the study period is also examined. While contending that British Administration was largely exploitative and resulted in a monumental disruption of the pre-colonial economic structure of the Ekiti society, it identifies certain sectors where the British Administration achieved some measure of development. The study concludes that though the British Administration tried to consolidate itself in Ekitiland, their initial objective of rigid political centralisation that would have brought Ekiti Kingdoms under one central authority was not realised. Furthermore, it observes that British Administration was a mixed blessing to the people of Ekltiland. The Ekiti accepted some of the changes considered beneficial to their society while rejecting those they considered detrimental to their well-being. The thesis has complemented the existing studies on British Administration in Nigeria in general and has also revealed the abysmal failure of British attempt to create a Central Administration in a society which was hitherto apparently segmentary.